A Computerized Standard Protocol Order Entry for Pediatric Inpatient Acute Seizure Emergencies Reduces Time to Treatment. (February 2014) - Xie, Yi; Morgan, Robin; Schiff, Linda; Hannah, Debbie; Wheless, James
Time to treatment of seizures is critical to efficacy. We performed a quality initiative and evaluated time to treatment of inpatient seizure emergencies with first- and second-line medicines before and after implementation of a computerized, standard treatment protocol. Data from 125 patients revealed that 179 seizure episodes required first-line antiepileptic drugs, and the mean time to treatment was 7.72 minutes. In 87 episodes, patients (49%) received the drugs within 5 minutes. Forty-six episodes required second-line drugs. In 17 (37%), patients received them within 30 minutes (mean 49.48 minutes). After implementation of the protocol, the mean time to treatment with first-line drugs was 3.74 minutes, a reduction of >50% ( P < .0001). The mean time to treatment with second-line drugs was 25.05 minutes, a reduction of ∼50% ( P < .0001). This effective model for reducing the time to treatment of seizure emergencies may be useful to similar institutions.